Characterization of lncRNA-protein interactions associated with Prostate cancer and Androgen receptors by molecular docking simulations - Barkha Khilwani; Bhumandeep Kour; Nidhi Shukla; Sugunakar Vuree; Abdul S. Ansari; Nirmal K. Lohiya; Prashanth Suravajhala; Renuka Suravajhala (Biochemistry and Biophysics Reports)
Long non-coding RNA (lncRNAs) are known to be implicated in pathogenesis of a broad spectrum of malignancies. These are found to have a significant role as signal transduction mediators in cancer signaling pathways. Prostate Cancer (PCa) is emerging with increasing cases worldwide even as advanced approaches in clinical diagnosis and treatment of PCa are still challenging to address. To enhance patient stratification, there is an indefatigable need to understand risk that can allow new approaches of treatment based on prognosis. While PCa is known to have mediated androgen receptor (AR) stimulation, the latter plays a critical role in regulating transcription of genes via nuclear translocation which in turn leads to response to androgens. LncRNAs have been implicated in developing clinical diagnostic and prognostic biomarkers in a broad spectrum of cancers. In our present study, 12 lncRNAs identified from clinical samples from our erstwhile PCa patients were docked with PCa and AR targeted 36 proteins. We identified three lncRNAs, viz. SCARNA10, NPBWR1, ANKRD20A9P are common between the targeted proteins and discern that SCARNA10 lncRNA could serve as a prognostic signature for PCa and AR biogenesis. We also sought to check the coding potential of interfacial residues associated with lncRNA docking sites.